Kultivasi Mikroalga Galdieria sp. dalam Limbah Gula (Molases) - Stivanus Anggara Kurniawan; Titik Budiati; Delicia Yunita Rahman (Politeknik Negeri Jember, 2023)
Microalgae have good potential in the food sector. Microalgae cultivation was carried out to obtain as much biomass as possible. Microalgae biomass contains carbohydrates, proteins, and lipids. This study aims to determine the effect of providing a carbon source in the form of waste sugar (molasses) on the carbohydrate, protein and lipid content of Galdieria sp. microalgae. The cultivation method used is the batch culture method, namely cultivation without continuous addition of media. Cultivation used 5 treatments with 3 replications. The results obtained from this study were that the concentration of 5% molasses waste had a significant effect on the content of carbohydrates, proteins and lipids